Between Convent Chores and Mystical Raptures: The Spiritual Diary of Ursula de Jesus (Lima, Seventeenth Century) - Pignano Bravo, Giovanna (2017)
The present article studies the case of the black donada Ursula de Jesus (Lima, 1604-1666), whose exceptional religiosity was described by a Franciscan friar and nun, both anonymous. She spent the greater part of her life inside the convent of Santa Clara, which she entered as the slave of a nun of the black veil. Later she obtained her liberty and, supported by certain nuns, entered as a donada. She went on to write a Spiritual Diary in which she described her everyday life in the convent and the vicissitudes of her spirituality. While we know of other Afro-descendants who were recognized for their piety, we know them only through the dominant discourse that shaped their individual experiences to make them fit the models of Western sanctity. In this case, it is the opposite: the Spiritual Diary allows us to hear the voice of an Afro-descended woman. Through an analysis of the Spiritual Diary, written between 1650 and 1661 and published in Lima in 2004, this article studies the identity that Ursula de Jesus constructs in her text, which reinterprets the reigning Catholic dogma and constructs a Black mystical spirituality.